ADVERSE EVENTS FOLLOWING PENTAVALENT VACCINE ADMINISTRATION: A DESCRIPTIVE STUDY IN THE INDIAN CONTEXT: Kejadian Ikutan Pasca Imunisasi (KIPI) Setelah Pemberian Vaksin Pentavalen: Studi Deskriptif dalam Konteks India - Sharma, Roop; Sharma, Bhanupriya; Saini, Yashu; Bairwa, Ramesh; Kakkar, Munish (Jurnal Berkala Epidemiologi, 2025)
Background: Immunization is one of the best ways to prevent childhood diseases. The pentavalent vaccine protects against five serious illnesses with fewer injections. It is cost-effective and usually causes fewer adverse events following immunization (AEFI). However, there are still limited data on AEFI after giving the pentavalent vaccine, compared to giving the DPT, Hep-B, and Hib vaccines separately. Purpose: To determine the proportion and factors associated with adverse events following immunization with pentavalent vaccines. Methods: This was a descriptive study conducted at an immunization clinic in a tertiary care center in India between January 2023 and December 2023. The study population consisted of all infants attending the clinic for vaccination, and all eligible infants receiving pentavalent vaccines were included in the study. The study was done to understand the frequency and type of AEFIs and to ensure the vaccine safety. Results: A total of 93 infants were included in this study, and 264 adverse events were noted in our study. Fever was the most common presenting adverse effect (22.73 %), other adverse effects were pain at injection site (21.21%), swelling at injection site (15.53%), redness at site of injection (14.39%), 10.60% held their leg back due to pain, persistent crying (9.47%) and abscess formation (4.55 %.), and seizures (1.52%). Conclusion: Most of the adverse effects observed in present study were of mild nature and of non-serious type. No major AEFI or permanent damage was noted in our study. The benefits of vaccination far outweigh the risks.